2013
DOI: 10.1287/isre.1120.0466
|View full text |Cite
|
Sign up to set email alerts
|

Active Social Media Management: The Case of Health Care

Abstract: Given the demand for authentic personal interactions over social media, it is unclear how much firms should actively manage their social media presence. We study this question empirically in a healthcare setting. We show empirically that active social media management drives more user-generated content. However, we find that this is due to an increase in incremental user postings from an organization's employees rather than from its clients. This result holds when we explore exogenous variation in social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(35 citation statements)
references
References 36 publications
3
31
1
Order By: Relevance
“…In fact, despite the prevalent positive e↵ects found in research, some studies show that involvement by peers might have negative e↵ects on targeted behaviors, such as the negative e↵ects found in Hildebrand et al (2013) is supported by the exit surveys where a few participants in the peer-enabled arms reported that they did not feel comfortable sharing their eating habits with strangers. Our results also imply that the contents of posts are important determinants of user engagement, as suggested by Miller and Tucker (2013), and need to be explore in future studies.…”
Section: Model Of User Engagementmentioning
confidence: 68%
“…In fact, despite the prevalent positive e↵ects found in research, some studies show that involvement by peers might have negative e↵ects on targeted behaviors, such as the negative e↵ects found in Hildebrand et al (2013) is supported by the exit surveys where a few participants in the peer-enabled arms reported that they did not feel comfortable sharing their eating habits with strangers. Our results also imply that the contents of posts are important determinants of user engagement, as suggested by Miller and Tucker (2013), and need to be explore in future studies.…”
Section: Model Of User Engagementmentioning
confidence: 68%
“…Dijkmans et al (2015) demonstrate that corporates' online activities encourage consumers' social media use, which can enhance corporate reputation especially among non-customers. Miller and Tucker (2013) also find incremental engagement with social media of client and employees when organisations actively managing their social media presence. However, it…”
Section: Organisational Managementmentioning
confidence: 99%
“…how other behaviors or other audiences in social environments influence user content generation behavior. Existing research shows that user content generation behavior can be influenced by prior UGC [38,45,46,58], audience size [6], social management [44,63] and online interaction (or social ties) [24,62,70]. For example, Lee, Hosanagar and Tan [38] explore the different effects of prior ratings from friends and strangers, and find that higher prior ratings can increase the intention of users to give a higher rating and this effect is weaker when the prior ratings are from friends.…”
Section: Literature Reviewmentioning
confidence: 99%